Risk analysis of gas leakage in gas pressure reduction station and its consequences: A case study for Zahedan. Issue 5 (May 2021) - Dadkani, Peiman; Noorzai, Esmatullah; Ghanbari, AmirHossein; Gharib, Ali
Abstract: Industrial accidents have increased the importance of dealing with the risks of toxic exposure, fire and explosion. Despite the measures taken in the chemical industry to prevent accidents, the accidents occur often due to human error or process faults during repairs. Although several studies have been conducted on the accidents in the process industry, no research has modeled the risks caused by the leakage of toxic substances in the gas pressure reduction station. The consequences of gas leak and fire in Zahedan's gas pressure reduction station were investigated in Iran. This research aims to determine the safe range of the station and observe the safety measures required for the gas pressure reduction station in Zahedan. For modelling gas leak and fire, the ALOHA software was used to display the threat zone. In this research, with respect to the environmental data, the desired scenario was modeled. The results, based on two scenarios of gas leak and fire in both hot and cold seasons, indicate that the gas leak scenario in hot seasons and the fire scenario in cold seasons influence a larger region. Abstract : Gas leak; Fire; Gas pressure reduction station; Risk analysis; Toxic substances; ALOHA